Inventory Lot Sizing Decisions for Material Requirements Planning to Minimize Inventory Costs - Filscha Nurprihatin; Rafie Djajasoepena; Vanessa Bertholdo Vargas; Moacyr Machado Cardoso Junior; Ali Vaezi (JIEMS (Journal of Industrial Engineering and Management Systems), 2023)
Inventory control is one of the most important factors in achieving optimal organizational performance. Material Requirement Planning (MRP) is a common method used by businesses to manage inventories. This study focuses on a hydraulic firm that has been in operation since 2016. This research examines the planning of eleven components to get the best planning for the company. This study contributes to the integration of Moving Average (MA) and Exponential Smoothing (ES) forecasting techniques alongside the MRP and three lot sizing techniques, such as LFL, EOQ, and LUC. The minimum error values between MA and ES are evaluated and followed by the comparison between three lot sizing techniques. The result shows that ES (α=0.1) is selected as the best forecasting technique, and LUC presents the lowest total inventory cost. However, LUC is only 0.05 percent lower than what LFL presents. A larger difference is shown by EOQ with 14.57 percent higher than LUC which makes EOQ unlikely to be selected.